2014
DOI: 10.1109/map.2014.6931657
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis and Measurement of Frequency-Tuned and Impedance-Tuned Wireless Non-Radiative Power-Transfer Systems

Abstract: Abstract-This paper theoretically and experimentally investigates frequency-tuned and impedance-tuned wireless nonradiative power transfer (WNPT) systems. Closed-form expressions for the efficiencies of both systems, as a function of frequency and system (circuit) parameters, are presented. In the frequency-tuned system, the operating frequency is adjusted to compensate for changes in mutual inductance that occur for variations of transmitter and receiver loop positions. Frequencytuning is employed for a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…By substituting Equations (6), (9), and (12) into Equation 11, the system efficiency η S can be obtained.…”
Section: Topology Transmission Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…By substituting Equations (6), (9), and (12) into Equation 11, the system efficiency η S can be obtained.…”
Section: Topology Transmission Parametersmentioning
confidence: 99%
“…Many works [12][13][14][15][16][17][18][19] have been done to improve the performance of the WPT system with uncertain parameters. In [12], an adaptive frequency-tracking technique is proposed to address coil distance and orientation variations. Through the method, the WPT system can maintain nearly constant efficiency when the user moves the receiver within a short range.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetically coupled loops, when resonated out, was proposed for use in midrange power transfer [1,3]. It has been shown that one can transfer power at a distance several times the radius or the length of the loops in magnetically coupled resonant loops [4,5]. Moreover, when the loops operate in a strongly coupled regime, it is almost possible to achieve a distance-independent power transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%